Is It Good to Have a Stiff Aorta with Aging? Causes and Consequences - Pierce, Gary L; Coutinho, Thais A; DuBose, Lyndsey E; Donato, Anthony J (Physiology (Bethesda, Md.), 2022)
Aortic stiffness increases with advancing age, more than doubling during the human life span, and is a robust predictor of cardiovascular disease (CVD) clinical events independent of traditional risk factors. The aorta increases in diameter and length to accommodate growing body size and cardiac output in youth, but in middle and older age the aorta continues to remodel to a larger diameter, thinning the pool of permanent elastin fibers, increasing intramural wall stress and resulting in the transfer of load bearing onto stiffer collagen fibers. Whereas aortic stiffening in early middle age may be a compensatory mechanism to normalize intramural wall stress and therefore theoretically "good" early in the life span, the negative clinical consequences of accelerated aortic stiffening beyond middle age far outweigh any earlier physiological benefit. Indeed, aortic stiffness and the loss of the "windkessel effect" with advancing age result in elevated pulsatile pressure and flow in downstream microvasculature that is associated with subclinical damage to high-flow, low-resistance organs such as brain, kidney, retina, and heart. The mechanisms of aortic stiffness include alterations in extracellular matrix proteins (collagen deposition, elastin fragmentation), increased arterial tone (oxidative stress and inflammation-related reduced vasodilators and augmented vasoconstrictors; enhanced sympathetic activity), arterial calcification, vascular smooth muscle cell stiffness, and extracellular matrix glycosaminoglycans. Given the rapidly aging population of the United States, aortic stiffening will likely contribute to substantial CVD burden over the next 2-3 decades unless new therapeutic targets and interventions are identified to prevent the potential avalanche of clinical sequelae related to age-related aortic stiffness.